Synthesis of organoamine-silica hybrids using cashew nut shell liquid components as templates for the catalysis of a model Henry reaction - Msigala, SC; Mdoe, JEG (Tanzania Journal of Science, 2021)
Organoamine-silica hybrids were prepared by a co-condensation of tetraethoxysilane (TEOS) and different aminoalkoxysilanes, namely, 3-aminopropyltrimethoxysilane, N-(3(trimethoxysilyl)propyl)-ethylenediamine and 3[2(2-amino)ethylamino]propyl trimethoxysilane, at different ratios using cashew nut shell liquid (CNSL) components as templates. Of the major components of CNSL tested, only cardanol was found to be efficient as a template as it yielded 66% of the hybrid. The prepared materials were characterized by diffuse reflectance Fourier Transform Infrared (FTIR), Atomic Force Microscopy and acid titration. Results indicated that indeed the organoamine groups were attached onto the silica surface, with a maximum loading of 2.9 mmol organic group per g silica. The materials were found to be very active as catalysts in a model Henry reaction, with yields ranging from 81% to 98%. The catalytic efficiency was found to depend on the type of template, amount of loading, type of aminoalkoxysilanes incorporated onto the silica framework and the ratio of aminoalkoxysilane to TEOS. Keywords: Organoamine-silica hybrids, micelle templated silica, cashew nut shell liquid